Structural properties of discs and bulges of early-type galaxies - de Jong, R; Simard, L; Davies, R; Saglia, R; Burstein, D; Colless, M; McMahan, R; Wegner, G (2004)
We have used the EFAR sample of galaxies to investigate the light distributions of early-type galaxies. We decompose the two-dimensional light distribution of the galaxies in a flattened spheroidal component with a Sérsic radial light profile and an inclined disc component with an exponential light profile. We show that if we assume that all galaxies can have a spheroidal and a disc component, then the brightest, bulge-dominated elliptical galaxies have a fairly broad distribution in the Sérsic profile shape parameter n B, with a median of approximately 3.7 and with σ ∼ 0.9. Other galaxies have smaller n B values. This means that spheroids are in general less concentrated than the de Vaucouleurs R 1/4-law profile, which has n B = 4. While the result of our light decomposition is robust, we cannot prove without kinematic information that these components are spheroids and discs, in the usual sense of pressure- and rotation-supported stellar systems. However, we show that the distribution of disc inclination angles is consistent with a random orientation if we take our selection effects into account. If we assume that the detected spheroids and discs are indeed separate components, we can draw the following conclusions: (1) the spheroid and disc scale sizes are correlated; (2) bulge-tototal luminosity ratios, bulge effective radii and bulge n B values are all positively correlated; (3) the bivariate space density distribution of elliptical galaxies in the (luminosity, scale size)plane is well described by a Schechter luminosity function in the luminosity dimension and a lognormal scale-size distribution at a given luminosity; (4) at the brightest luminosities, the scale size distribution of elliptical galaxies is similar to those of bright spiral galaxies, but extending to brighter magnitudes; at fainter luminosities the scale size distribution of elliptical galaxies peaks at distinctly smaller sizes than the size distribution of spiral galaxies; and (5) bulge components of early-type galaxies are typically a factor of 1.5-2.5 smaller than the discs of spiral galaxies with a slight luminosity dependence, while disc components of early-type galaxies are typically twice as large as the discs of spiral galaxies at all luminosities.